Mixed Copper States in Anodized Cu Electrocatalyst for Stable and Selective Ethylene Production from CO2 Reduction - Lee, Si Young; Jung, Hyejin; Kim, Nak-Kyoon; Oh, Hyung-Suk; Min, Byoung Koun; Hwang, Yun Jeong (AMER CHEMICAL SOC, 2018)
OxygenCu (OCu) combination catalysts have recently achieved highly improved selectivity for ethylene production from the electrochemical CO2 reduction reaction (CO2RR). In this study, we developed anodized copper (AN-Cu) Cu(OH)(2) catalysts by a simple electrochemical synthesis method and achieved similar to 40% Faradaic efficiency for ethylene production, and high stability over 40 h. Notably, the initial reduction conditions applied to AN-Cu were critical to achieving selective and stable ethylene production activity from the CO2RR, as the initial reduction condition affects the structures and chemical states, crucial for highly selective and stable ethylene production over methane. A highly negative reduction potential produced a catalyst maintaining long-term stability for the selective production of ethylene over methane, and a small amount of Cu(OH)(2) was still observed on the catalyst surface. Meanwhile, when a mild reduction condition was applied to the AN-Cu, the Cu(OH)(2) crystal structure and mixed states disappeared on the catalyst, becoming more favorable to methane production after few hours. These results show the selectivity of ethylene to methane in O-Cu combination catalysts is influenced by the electrochemical reduction environment related to the mixed valences. This will provide new strategies to improve durability of O-Cu combination catalysts for C-C coupling products from electrochemical CO2 conversion.
Keywords: ELECTROCHEMICAL REDUCTION; CARBON-DIOXIDE; ELECTROREDUCTION; EFFICIENT; FILMS; OXIDATION; METAL; NANOPARTICLES; DEACTIVATION; ELECTRODES